1966
DOI: 10.1180/claymin.1966.006.3.04
|View full text |Cite
|
Sign up to set email alerts
|

Organo-metallic clay complexes

Abstract: Differential thermal analysis curves were obtained for a series of diamine and glycol complexes with natural and copper substituted montmorillonite, in air and in an inert atmosphere. Thermobalance curves of the diamine-clay systems were also determined. The exothermic peaks observed in air are characteristic for any particular system and reflect the nature and binding of the interlamellar material; no direct correlation was, however, observed with pyrolysis and oxidation processes in the clay. Organic matter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1967
1967
1995
1995

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Studies of the sorption of amines and catechols by montmorillonite containing exchangeable transition metal ions, particularly copper, showed that there is a strong tendency to complex formation in the clay interlayers (Bodenheimer et al, 1962;Bodenheimer, Kirson & Yariv, 1963;Bodenheimer, Heller & Yariv, 1963a, b, 1964, 1966a, b, 1967. Amines, particularly diamines, can be extracted by copper *Present address: Department of Geology, Hebrew University, Jerusalem.…”
mentioning
confidence: 99%
“…Studies of the sorption of amines and catechols by montmorillonite containing exchangeable transition metal ions, particularly copper, showed that there is a strong tendency to complex formation in the clay interlayers (Bodenheimer et al, 1962;Bodenheimer, Kirson & Yariv, 1963;Bodenheimer, Heller & Yariv, 1963a, b, 1964, 1966a, b, 1967. Amines, particularly diamines, can be extracted by copper *Present address: Department of Geology, Hebrew University, Jerusalem.…”
mentioning
confidence: 99%
“…Ligand competition for metal ions is always occurring, but this decreased adsorption can be compensated by other forms ofligand-metal-solid interactions: The formation of ternary complexes promotes metal adsorption at oxide minerals (Schindler and Stumm, 1987;Schindler, 1990). For clay minerals, an enhanced uptake of cationic metal-ligand complexes by ion-exchange as compared with the free metal ion has been reported (Bodenheimer et al, 1962(Bodenheimer et al, , 1963(Bodenheimer et al, , and 1966Cloos et al, 1972;Maes et al, 1978). This effect was interpreted as a stabilization of the metal-ligand complex by the interlayer phase as compared with the aqueous solution (Maes et al, 1978).…”
Section: Introductionmentioning
confidence: 97%
“…They have been extensively investigated by Bodenheimer and coworkers [5,6,7]. The second gr oup derivatives were reported for the first time by Smith and Hendricks [8,9] and consequently studied extensively .…”
Section: Introductionmentioning
confidence: 97%